Towards a transformational transdidactic in the educational act. - Cartaya, Miguel (Conexiones UG, 2023)
In this study, it is proposed why the didactic reconfiguration should become the daily task of every teacher, based on the search for real and socially relevant meanings. For this reason, a hermeneutic reflection is made about the lack of knowledge in the today’s times, facing the chllenges and challenges that the educational and investigative fact implies in the world, from a study of hermeneutic modality, from which it becomes possible to promote options other than didactics, according to the newsocio-educational challenges that It propels a didactic reconfiguration with new perspectives, reinterpretations and redefinitions of the educational task, for educational work in which the ontological is erected to blur what has defined the colonizing didactic thought. Hence, educational methodological assumptions are advocated that overcome and transgress theepistemological and even sociocultural obstacles that prevent the teaching intellect from acting in and from a process in which it is not taught but shared and permanent knowledge is built and deconstructed. Thus, it is concluded that the transepistemology of the didactics of the teaching-learning loop requires taking into account not only the act of teaching itself, but all those involved in said act and that is why Transdidactics takes into account the student, the teacher, planning, curriculum, teaching techniques, content, among others.
Keywords: Transdidactics; Transformational Educational Act